Mama Illegal - Moschitz, Ed (Austria, 2011)
They leave their humble homes, the broken roads, the dilapidated schools and the countless abandoned houses behind to work in Austria or Italy as cleaners or care workers. Here they live a life in the underground - a tough job, without valid documents, unprotected and without health care - separated from their children and families for years. They send the little that remains of their hard-earned Western money home to their families. But their desire for a brighter future and a better life comes at a high price: after a long time away from home, the children are grown up and their husbands estranged. The social gulf that they sought to overcome threatens to tear apart the families once and for all. Having never really arrived or been accepted in the West, they find that they have become alienated from their homeland. Mama Illegal portrays seven years in the lives of three women. The camera is present during tragedies as well as in moments of joy. A film about the price of the dream of a better life.
Verzio Film Festival Submission
Verzio Film Festival Submission
Keywords: Documentary films